Investigating the accessibility factors that influence antenatal care services utilisation in Mangwe district, Zimbabwe - Leoba Nyathi; Augustine K. Tugli; Takalani G. Tshitangano; Molyn Mpofu (AOSIS, 2017)
Background: Maternal and infant mortality remains a huge public health problem in developing countries. One of the strategies to minimise the risks of both maternal and infant mortality is access to and utilisation of antenatal care (ANC) services. Aim: This study aimed to investigate the accessibility factors that influence the use of ANC services in Mangwe district. Methods: A qualitative approach using explorative design was adopted to target women who have babies under 1 year of age. The study was conducted in Mangwe district, Matabeleland South province, Zimbabwe. Data were collected through semi-structured interviews and observations. Data saturation was reached after 15 women who were conveniently sampled were interviewed. Field notes were analysed thematically using Tech's steps. Lincoln and Guba's criteria ensured trustworthiness of the study findings. Results: Accessibility factors such as lack of transport, high transport costs and long distances to health care facilities, health care workers' attitudes, type and quality of services as well as delays in receiving care influence women's utilisation of ANC services in Mangwe district, Zimbabwe. Conclusion: The study concluded that women were still facing problems of unavailability of nearby clinics; therefore, it was recommended that the government should avail resources for women to use. Recommendations: Mangwe District Health Department should provide mobile clinics rendering ANC services in distant rural areas.